Ability of Linezolid to Combat Staphylococcus aureus and Pseudomonas aeruginosa Isolated from Polymicrobial Wound Infections - Samar A. Ahmed; Vy T. Luu; Teresa C. Oyono Nsuga; Steven E. Burgos; Eugene Kreys; Jered Arquiette; Justin R. Lenhard (Antibiotics)
Background/Objectives: The optimal therapy for polymicrobial wound infections is poorly defined. We sought to characterize the ability of linezolid to combat mixed cultures of Staphylococcus aureus and Pseudomonas aeruginosa. Methods: The antistaphylococcal activity of linezolid was assessed in 24-h time-killing experiments that used S. aureus and P. aeruginosa isolated from polymicrobial wound infections. Clindamycin was also evaluated as a comparator. A Hill-type mathematical model was used to assess the maximum killing of S. aureus (Emax). The ability of linezolid to potentiate the activity of host defense peptides against P. aeruginosa was evaluated using LL-37. Results: In the presence of P. aeruginosa, the Emax of linezolid decreased in 5/9 co-culture experiments and increased in 4/9 co-culture experiments in comparison to linezolid against S. aureus alone. The potency of linezolid was not significantly impacted by the presence of P. aeruginosa. In comparison, the maximal S. aureus killing achieved by clindamycin decreased in eight out of nine experiments, and somewhat paradoxically, the potency increased in nine out of nine experiments. In the host defense peptide assay, the supratherapeutic linezolid concentration of 64 mg/L did not significantly enhance the killing of the LL-37 peptides (p ≥ 0.121), but the concentration of linezolid was significantly associated with the killing of one of three P. aeruginosa isolates (p = 0.005). Conclusions: P. aeruginosa had a minimal impact on the antistaphylococcal activity of linezolid in comparison to clindamycin. Linezolid did not exert a consistent ability to enhance the antipseudomonal activity of host defense peptides. These data may help inform antimicrobial selection during polymicrobial wound infections.